Trust-aware dynamic level scheduling algorithm in cloud environment - Jie CAO; Guo-sun ZENG; Huo-wen JIANG; Hai-ying MA (Tongxin xuebao)
Based on interpersonal trust model in sociology，a trust evaluation model is proposed based on users’ past experience with service provider，friends’ recommendations and third party’s feedback.By combining users’ trust requirement for service resource together with trust degree of service resource and dynamic level scheduling(DLS) algorithm，a novel scheduling algorithm was proposed that was called trust-aware dynamic level scheduling algorithm in cloud environment(CTDLS).The algorithm takes the cloud service resources’ trust degree into account when calculates the scheduling-level of task-resource pairs.The simulation experimental results show that such algorithms can effectively satisfy the tasks’ trust requirement and improve the success rate of parallel tasks scheduling in practice.